2017
DOI: 10.1515/ijcre-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Activity of TiO2 Degussa P25 and Millennium PCs in the Photocatalytic Degradation of Bromothymol Blue

Abstract: The photocatalytic activities of TiO2 Degussa P25 and Millennium PCs (PC50, PC100, PC105 and PC500) were evaluated by the photocatalytic degradation of Bromothymol Blue (BTB). The relationship between the photocatalytic reaction and the adsorption of BTB on the TiO2 catalysts at acidic, natural and basic mediums of pH was investigated. The crystalline phase, average crystalline size and surface area of the catalyst were found to have a significant influence on the adsorption and photocatalytic activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…This small surface area suggests rather low adsorption properties. This is consistent with the study (Bouanimba et al 2018) which showed that the P25 photocatalyst is not able to adsorb the dye Bromothymol Blue and it provides much faster photodegradation compared to other TiO 2 samples. Moreover, previous studies have shown that the P25 photocatalyst provides rapid degradation of many organic compounds (Katal et al 2020).…”
Section: Xrd and Bet Analysissupporting
confidence: 92%
“…This small surface area suggests rather low adsorption properties. This is consistent with the study (Bouanimba et al 2018) which showed that the P25 photocatalyst is not able to adsorb the dye Bromothymol Blue and it provides much faster photodegradation compared to other TiO 2 samples. Moreover, previous studies have shown that the P25 photocatalyst provides rapid degradation of many organic compounds (Katal et al 2020).…”
Section: Xrd and Bet Analysissupporting
confidence: 92%
“…Degussa P25, a commercially available TiO 2 , is one of the most efficient photocatalysts in terms of cost and photocatalytic ability, with a number of works published elsewhere [ 7 , 8 , 9 , 10 , 11 ]. Despite that, these studies reported some issues with this particular photocatalyst, and one of them is the high bandgap energy (~3.2 eV) The high bandgap value limits the light utilization efficiency and reduces the number of electrons that could participate in the redox reaction, which consequently deteriorates the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The XRD spectra of the obtained nanoparticles are shown in Fig. 2 Crystallite size was obtained by Debye-Scherrer formula given by equation [16,20]:…”
Section: Xray Diffractometry (Xrd)mentioning
confidence: 99%
“…In addition, another reason can explain these results is that after the addition of HCO − 3 ions, CO •− 3 radicals has been formed in the solution, since carbonate radicals can attack the dye molecules and enhance the photocatalytic reaction, however, the CO •− 3 radicals are less reactive than • OH radicals [16].…”
Section: Effect Of Hco − 3 Additionmentioning
confidence: 99%
See 1 more Smart Citation